2021
DOI: 10.3390/plants10102155
|View full text |Cite
|
Sign up to set email alerts
|

Woody and Foliage Biomass, Foliage Traits and Growth Efficiency in Young Trees of Four Broadleaved Tree Species in a Temperate Forest

Abstract: The main goal of this study is to analyse and interpret interspecific differences in foliage biomass/area and woody parts biomass as well as the ratio between quantities of foliage and woody components (i.e., branches, stem and roots). The study was principally aimed at determining basic biomass allocation patterns and growth efficiency (GE) of four broadleaved species, specifically common aspen (Populus tremula L.), European hornbeam (Carpinus betulus L.), silver birch (Betula pendula Roth.) and sycamore (Ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…At the same time, the plot-level LAR was between 4.0 and 10.6 cm 2 per g of total plant dry mass. Our previous study [24], focusing on SLA at the tree level, showed that European hornbeam had lower values for SLA and LAR than three other broadleaved species (Acer pseudoplatanus L., Betula pendula Roth and Populus tremula L.).…”
Section: Importance Of Leaf Traitsmentioning
confidence: 95%
See 1 more Smart Citation
“…At the same time, the plot-level LAR was between 4.0 and 10.6 cm 2 per g of total plant dry mass. Our previous study [24], focusing on SLA at the tree level, showed that European hornbeam had lower values for SLA and LAR than three other broadleaved species (Acer pseudoplatanus L., Betula pendula Roth and Populus tremula L.).…”
Section: Importance Of Leaf Traitsmentioning
confidence: 95%
“…Our literature search suggested that results on the LAR, SLA and LAI of European hornbeam were still sparse. On the currently available information on European hornbeam, the LAR and SLA are represented at either the leaf or tree level [24] but nothing is available for the stand level.…”
Section: Introductionmentioning
confidence: 99%